EVALUASI KINERJA LAPORAN KEUANGAN SAHAM BJTM DAN BJBR - Hartono, Wendra (Widya Mandala Surabaya Catholic University, 2020)
In the banking world is the front line in the world of leading economy in Indonesia. Several major activities in the banking business sector are related to the number growth of rate interest or credit, inflation rate, bond, digital financial services, term deposit, mutual fund and other instruments. BJBR and BJTM, are categorized as a local government bank which had long been on the floor market since 2010 and 2012. Both of bank shares has been targeted by investors, it is due to their performance are better by the time goes by and the number of dividend per share also constantly high and price per share is still cheap. The aim of this research is more about evaluation of BJBR and BJTM’s performances either in fundamental or technical analysis sides also news or fact from these stocks since 2016. The method used in this study is qualitative descriptive, which explore the important incidents occurred. The result of this research shows that BJBR share has better performance and financial report compared to BJTM. Nevertheless, it is still needed to be considered that price per share of BJTM is much cheaper than BJBR.